2004
DOI: 10.1007/s00170-002-1469-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of a finite element model for the chemical mechanical polishing process

Abstract: In this paper, relative velocity at a given point on the wafer was first derived. The revolutions of wafer and pad are assumed the same and the axisymmetric uniformly distributed pressure form is given. Thus, a 2D axisymmetric quasic-static model for chemical-mechanical polishing process (CMP) was established. Based on the principle of minimum total potential energy and axisymmetric elastic stress-strain relations, a 2D axisymmetric quasic-static finite element model for CMP was thus established. In this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…4a shows the correlation between the calculated von Mises stress distributions and the distance from the wafer centre. [8] To understand much more about the variations of the lower and flatter parts of the von Mises stress distributions in Fig.4a, the scale in the y axis of this part is magnified and plotted in Fig.4b. Figs.…”
Section: A Verification Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…4a shows the correlation between the calculated von Mises stress distributions and the distance from the wafer centre. [8] To understand much more about the variations of the lower and flatter parts of the von Mises stress distributions in Fig.4a, the scale in the y axis of this part is magnified and plotted in Fig.4b. Figs.…”
Section: A Verification Of the Modelmentioning
confidence: 99%
“…The profile of the stress distribution is similar to that described by Wang et al [6], but the site of the peak stress is somewhat different. Lin and Lo [8] established a two-dimensional axisymmetric quasicstatic model for CMP and developed a two-dimensional axisymmetric quasic-static finite element model for CMP. They found that the profile of the simulated von Mises stress distributions is similar to that of the experimental removal rate.…”
Section: Introductionmentioning
confidence: 99%
“…This is the equivalent of saying that every asperity is compressed within itself without expanding laterally. Although the pad material will expand under compression, we estimate the strain to be about 0.03 and therefore negligible, assuming Poisson's ratio for our surface is no greater than 0.1 [19]. Figure 3 is a cross section of the original Gaussian surface, which is shaded in dark gray.…”
Section: Simulationmentioning
confidence: 99%
“…[1][2][3][4] The CMP is based on a rotating table, a polishing head and a suspension pad, where the surface of the wafer moves across the pad, under pressure, in the presence of slurry abrasive. The mechanical movement and the downward force are applied to the wafer by the machine.…”
Section: Introductionmentioning
confidence: 99%